2021
DOI: 10.1186/s40001-021-00518-6
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of chest wall glomus tumor presenting with axillary pain: a case report and literature review

Abstract: Background Glomus tumor is an uncommon soft tissue tumor. However, as the tumor causes significant disability, its early diagnosis is essential. It involves subungual areas of fingers and toes in most cases, and its extra-digital involvement is rarely seen. To the best of the authors' knowledge, only a few chest wall involvement cases have been reported in the literature. Case presentation In this paper, we describe a 63-year-old patient with a che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…While previous cases have described glomus tumors involving the chest wall, this is the first reported case within the costal joint. Other instances of thoracic involvement also noted the presence of coughing, which may be a contributing factor [11,12]. Management of glomus tumors entails complete surgical removal of the lesion, proving curative in most cases [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous cases have described glomus tumors involving the chest wall, this is the first reported case within the costal joint. Other instances of thoracic involvement also noted the presence of coughing, which may be a contributing factor [11,12]. Management of glomus tumors entails complete surgical removal of the lesion, proving curative in most cases [12].…”
Section: Discussionmentioning
confidence: 99%
“…Other instances of thoracic involvement also noted the presence of coughing, which may be a contributing factor [11,12]. Management of glomus tumors entails complete surgical removal of the lesion, proving curative in most cases [12]. Recurrence can occur, often within a year of excision, and is usually attributed to insufficient removal rather than true recurrence [13].…”
Section: Discussionmentioning
confidence: 99%
“…Glomus tumors are rare mesenchymal neoplasms arising from the glomus body [ 8 ]. GTs typically develop between the 3rd and the 5th decade of life [ 9 ]. Due to the higher density in glomus bodies, the subungual area of the digits, is the most common anatomical area of GT development [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision remains the standard of care resulting to the immediate resolution of the symptoms and the minimization of recurrence risk [ 15 ]. Previous series reported that after GT resection a 10–30% recurrence rate should be expected [ 9 ]. However, in a review by Geramizadeh et al.…”
Section: Discussionmentioning
confidence: 99%
“…It regulates the body's temperature and blood pressure through arteriovenous flow. 1,2,4,[6][7][8] Glomus tumour was originally described as 'painful subcutaneous tubercle' by Wood in 1812. 9 In 1924, Mason et al named glomus tumour following a histopathology analysis.…”
Section: Introductionmentioning
confidence: 99%